Peningkatan Minat Belajar Peserta Didik Melalui Media Qosidah Kimia pada Materi Senyawa Karbon dan Makromolekul - Muhammad Nur Mukhayya; Woro Sumarni (Journal Prakarsa Paedagogia, 2025)
This study was motivated by the low level of students’ interest in learning chemistry, particularly in the topic of carbon compounds and macromolecules, which are often perceived as abstract, complex, and difficult to understand. Such perceptions frequently lead to passive learning behavior and limited conceptual engagement. To address this issue, an instructional innovation was implemented through the use of chemical qasidah media, which integrates elements of art, local culture, and religiosity into the chemistry learning process. The study employed a Classroom Action Research (CAR) design based on the Kemmis and McTaggart model, conducted in two iterative cycles involving planning, action, observation, and reflection. The participants were 30 eleventh-grade science students at MA NU Tasywiquth Thullab Salafiyah (TBS) Kudus during the 2025/2026 academic year. Data were collected using a validated learning interest questionnaire, structured observation sheets, and supporting documentation. Quantitative data were analyzed using percentage techniques, while qualitative data were examined through reflective analysis. The findings revealed a consistent increase in students’ learning interest, rising from 56% in the pre-cycle (moderate category) to 71% in the first cycle (sufficient category), and reaching 84% in the second cycle (high category). The improvement was particularly evident in students’ attention, participation, and enthusiasm during learning activities. These results indicate that the integration of chemical qasidah as a culturally responsive and affective-based learning medium is effective in enhancing students’ interest in learning complex chemistry concepts